Prevalence of Neisseria meningitidis carriers in the school population of Catalonia, Spain. - Domínguez, A. (Cambridge University Press, 2001)
The aim of this study was to determine the prevalence of healthy Neisseria meningitidis pharyngeal carriers in a representative sample of the Catalonian school population, as well as its associated factors. The sample was divided into age groups: < or = 5, 6-7 and 13-14 years old. Parents were given a questionnaire to collect information on sociodemographic and epidemiological variables. Oropharyngeal swabs were collected with a cotton-tipped swab in an Amies transport medium and cultured on Thayer Martin plates at 35 degrees C in 5% CO2. The isolates were serogrouped and sero/subtyped. Of the 1406 children studied, 75 (5.34%) meningococcal carriers were detected: 63 B (4.5%), 9 non groupable (0.7%), 2 29E (0.1%) and 1X (0.07%). No serogroup C meningococci were found in this study, probably due to the high A+C vaccination coverage of up to 68.9% in children 6-7 years old. Bivariate analysis identified six statistically significant risk factors for meningococcal carriage: increasing age, recent upper respiratory tract infection, previous antibiotic treatment, number of students in the class, size of the classroom and social class. Multivariate analysis found that only age and previous antibiotic treatment remained statistically significant when the other factors were controlled.